Т. 49, № 10 : Приложение (2006, 2006)
Прил.: 2nd International Congress on Radiation Physics and Chemistry of Inorganic Materials, high current Electronics, and Modification of Materials with Particle beams and Plasma flows: 13 th RPC PROCEEDINGS: Tomsk, Russia, 10-15 September, 2006